2021
DOI: 10.1111/jocd.14579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety and efficacy of a new device for muscle toning and body shaping

Abstract: A large number of people of both sexes (about 80%) are affected by problems involving excess weight and localized adiposity. The risk of cancer or cardiovascular disease is increased due to abdominal obesity, which gives evidence of the presence of fat around the bowels. 1 The most effective and fast treatments for the remodeling of the body shape are certainly the surgical ones; also in 2017, liposuction was the most popular cosmetic surgical procedure. 2 Cosmetic surgery is undoubtedly the most effective as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…1). 5,10,11,[14][15][16]20,22 By contrast, the sham-controlled study by Samuels et al 6 showed a dramatic reduction in the abdominal profile (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…1). 5,10,11,[14][15][16]20,22 By contrast, the sham-controlled study by Samuels et al 6 showed a dramatic reduction in the abdominal profile (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The study subject device, with its handpieces, shown in Figure 5, adapts perfectly to the different areas of the body treated and transmits electromagnetic energy directly to the muscle tissue, contracting and releasing it. This type of stimulation is superior to that achievable voluntarily by the user and it is already successfully used for body remodeling with excellent results [17,31].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of the subject device include an increase in muscle tone and mass, maximum comfort, completely painless procedure, no recovery time, improvement of posture and the presence of pre-set and customized protocols. This type of stimulation is superior to that achievable voluntarily by the user and it is already successfully used for body remodeling with excellent results [17,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Notably, these body contouring techniques do not address underlying musculature, despite musculature representing a vital aspect of the sculpted physique. 3,4 Aesthetic muscle stimulation (AMS) by using high-intensity focused electromagnetic field (HIFEM) or direct electrical muscle stimulation (EMS) is becoming a popular treatment that can target both the musculature and adipose tissue for superior aesthetic outcomes. 5 The objective of this study was to provide a comprehensive review of magnet-based AMS techniques and critically evaluate the current literature on its use in noninvasive body contouring.…”
mentioning
confidence: 99%